Community based service providers' perspectives on frequent and/or avoidable admission of older people with chronic disease in rural NSW: a qualitative study - Ewald Dan P; Heathcote Kathy E; Pirotta Julie P; Passey Megan E; Barclay Lesley M; Gao Yu; Singer Judy B; Longman Jo M; Saberi Vahid; Corben Paul; Morgan Geoffrey G (BMC, 2011)
Abstract Background Frequent and potentially avoidable hospital admission amongst older patients with ambulatory care sensitive (ACS) chronic conditions is a major topic for research internationally, driven by the imperative to understand and therefore reduce hospital admissions. Research to date has mostly focused on analysis of routine data using ACS as a proxy for 'potentially avoidable'. There has been less research on the antecedents of frequent and/or avoidable admission from the perspectives of patients or those offering community based care and support for these patients. This study aimed to explore community based service providers' perspectives on the factors contributing to admission among older patients with chronic disease and a history of frequent and potentially avoidable admission. Methods 15 semi-structured interviews with community based providers of health care and other services, and an emergency department physician were conducted. Summary documents were produced and thematic analysis undertaken. Results A range of complex barriers which limit or inhibit access to services were reported. We classified these as external and internal barriers. Important external barriers included: complexity of provision of services, patients' limited awareness of different services and their inexperience in accessing services, patients needing a higher level or longer length of service than they currently have access to, or an actual lack of available services, patient poverty, rurality, and transport. Important internal barriers included: fear (of change for example), a 'stoic' attitude to life, and for some, the difficulty of accepting their changed health status. Conclusions The factors underlying frequent and/or potentially avoidable admission are numerous and complex. Identifying strategies to improve services or interventions for this group requires understanding patient, carer and service providers' perspectives. Improving accessibility of services is also complex, and includes consideration of patients' social, emotional and psychological ability and willingness to use services as well as those services being available and easily accessed.